Adsorption Behavior of Methylene Blue Onto Activated Coconut Shells: Kinetic, Thermodynamic, Mechanism and Regeneration of the Adsorbent - Moussa Abbas; Mohamed Trari (SAGE Publishing, 2024)
Adsorption techniques are widely used to remove some classes of pollutants from waters, especially those which are not easily biodegradable. The removal of Methylene blue (MB), as a pollutant, from waste waters of textile, paper, printing and other industries has been addressed by the researchers. The aim of this study is to eliminate MB by Activated Coconut Shells (ACS) produced at low cost by adsorption in batch mode. The ACS was characterized by the FTIR spectroscopy and point of zero charge (pHpzc: 5.06). Some examined factors were found to have significant impacts on the MB uptake of ACS like the initial dye concentration C o (40-120 mg/L), solution pH (2-8), ACS dose (1-12 g/L), agitation speed (50-500 r/min), particles size (1.0-1.2 mm) and temperature (298-333 K). The best capacity was found at pH 6 with an adsorbent dose 8 g/L, an agitation speed 200 r/min and a contact time of 60 min. Modeling Kinetics and Isotherms shows that the pseudo-second-order kinetic model with R 2 (0.935 -0.998) and Langmuir adsorption isotherm model provide better fitness to the experimental data with the maximum adsorption capacity of 30.30 mg/g at 25°C. The separation factor R L (0.933-0.541) in the concentration range studied (10-120 mg/L) shows a favorable adsorption. The isotherms at different temperatures have been used for the determination of the free energy ΔG ° (198-9.72 kJ/mol); enthalpy ΔH ° (82.082 kJ/mol) and entropy ΔS o (245.689 J/K mol) to predict the nature of MB adsorption process. The positive values of (ΔG o ) and (ΔH o ) indicate a non-spontaneous and endothermic MB adsorption with a chemisorption. The adsorbent elaborated from Coconut Shells was found to efficient and suitable for the removal of MB dye from aqueous solutions, due to its availability, low cost preparation and good uptake capacity.